2018
DOI: 10.1136/oemed-2018-104996
|View full text |Cite
|
Sign up to set email alerts
|

Metals in urine in relation to the prevalence of pre-diabetes, diabetes and atherosclerosis in rural India

Abstract: Our data suggest a probable role of metals in the aetiology of diabetes and cardiovascular diseases in rural communities. Identifying and eliminating the causes of increased levels of these environmental chemicals could have a beneficial impact on the burden of non-communicable diseases in rural population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…As for urinary Cr, the sum that T2D patients have higher levels of urinary Cr was the same as the proposition of Kazi et al [7] who proved no statistically significant difference as well but deemed the tendency existed; it elevated visibly in T1D; considering the severity of illness and thus selection being incomprehensive, prediabetes showed no significant difference comparing with the control group on urinary Cr level; the Cr/UCr in diabetic groups was lower than those of the prediabetic and control group, indicating diabetic patients were all under low Cr state. It is already proved in a research launching in Indian rural areas that elevated urinary Cr is strongly correlated to diabetes [29]; our experiment adopted a random urine specimen, which might have varied greatly due to physical and chemical factors; thus the statistical difference could not be that obvious. Besides, it is noticeable that the excretion rate of Cr and Fe changed mildly in DN patients, which was opposite to our expectation that severe renal function damaged influenced elements in urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for urinary Cr, the sum that T2D patients have higher levels of urinary Cr was the same as the proposition of Kazi et al [7] who proved no statistically significant difference as well but deemed the tendency existed; it elevated visibly in T1D; considering the severity of illness and thus selection being incomprehensive, prediabetes showed no significant difference comparing with the control group on urinary Cr level; the Cr/UCr in diabetic groups was lower than those of the prediabetic and control group, indicating diabetic patients were all under low Cr state. It is already proved in a research launching in Indian rural areas that elevated urinary Cr is strongly correlated to diabetes [29]; our experiment adopted a random urine specimen, which might have varied greatly due to physical and chemical factors; thus the statistical difference could not be that obvious. Besides, it is noticeable that the excretion rate of Cr and Fe changed mildly in DN patients, which was opposite to our expectation that severe renal function damaged influenced elements in urine.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that diabetes affected absorption, transportation, and utilization of Cr and Fe. The limitations of this experiment are that the number of enrolled cases was not enough and the prediabetic group consisted of outpatients; therefore it would be difficult to follow up; there is no more detailed research, such as disease-staging patients; in a way, a 24 h urine sample may be better than a random urine specimen, which reflects cumulative exposure, exposure approaches, and different forms of elements [29]; metabolism, lifestyle, or drugs may not be excluded from impact of exposure, absorption, or excretion of certain elements.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Very recently, Velmurugan et al revealed a strong association between diabetes and urinary levels of certain metals such as chromium and arsenic. [27] Such evidence indicates that diabetes mellitus may lead to increased urinary loss of chromium ions (Cr +3 ), which can lead over time to chromium deficiency. [25] Otherwise, a sequential randomized controlled cross-over study revealed that the loss of urinary chromium following the high glycemic-index diets, for 6 days, have not been observed in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The geographic location of the study areas is provided in Figure 1. Nallampatti is a typical farming village located around 60 km from Coimbatore 15,16 chosen as a representative rural area. Thadagam, a brick kiln rich area located 15 km from Coimbatore and Kalapatti, located within Coimbatore city, were chosen as representative sub‐urban and urban areas respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies from rural India indicated the huge burden of diabetes and its complications with association of environmental factors like heavy metals and pesticide exposure. 13‐18 However, it remains vital to understand disease patterns in different communities, as wide geographic variations in disease patterns are likely in a vast country like India. Such studies will have implications in redefining health policy specific to those regions and may also provide insights into novel pathophysiological mechanisms, as well as regional socio‐cultural factors that may be at play.…”
Section: Introductionmentioning
confidence: 99%